2022
DOI: 10.1021/acs.jpcc.2c00982
|View full text |Cite
|
Sign up to set email alerts
|

Intersystem Crossing and Electron Spin Dynamics of Photoexcited Bodipy Dimers

Abstract: Two Bodipy dimers were prepared (BDP-BDP and BDP-BDP-I2), with a phenyl unit as the linker between two Bodipy moieties. It was found that the triplet excited state of the first dimer depopulates fast to the ground state, while the metastable triplet state is well-detected in the second dimer. With two iodine atoms attached, a high singlet oxygen quantum yield (ΦΔ = 51.5%) and long intrinsic triplet state lifetime (τT = 210 μs) of BDP-BDP-I2 were observed in toluene, which are similar to those of diiodo Bodipy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…[9][10][11] At present, the main types of photosensitizers included the S/I atom substitution type, 12,13,72,73 metal coordination type, 14 nano-AIEgen type, 15 spin-orbit charge-transfer intersystem crossing (SOCT-ISC) type, 16 and multimer polymerization type. 17 Among these types of photosensitizers, the SOCT-ISC type photosensitizer was considered as the most promising photosensitizer 18 and there are three reasons for this. Firstly, the intersystem crossing (ISC) ability of the SOCT-ISC type photosensitizer is an inherent attribute and does not require heavy atom substitution or heavy metal coordination, 13,14 which could lead to lower cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] At present, the main types of photosensitizers included the S/I atom substitution type, 12,13,72,73 metal coordination type, 14 nano-AIEgen type, 15 spin-orbit charge-transfer intersystem crossing (SOCT-ISC) type, 16 and multimer polymerization type. 17 Among these types of photosensitizers, the SOCT-ISC type photosensitizer was considered as the most promising photosensitizer 18 and there are three reasons for this. Firstly, the intersystem crossing (ISC) ability of the SOCT-ISC type photosensitizer is an inherent attribute and does not require heavy atom substitution or heavy metal coordination, 13,14 which could lead to lower cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that the energy hopping increases the rate of flip-flop spin transitions between distant species. 15 During the past several years we have intensively studied rigid molecular conjugates with several chromophores [16][17][18] and studied a number of remarkable phenomena by transient optical and magnetic resonance spectroscopy. Recently, we have developed a model for the description of the evolution of the spin populations in molecular conjugates due to reversible transitions between nearly degenerate triplet states, which we denote as triplet exciton hopping.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the optical and time-resolved electron paramagnetic resonance (TREPR) spectra allows the presence of the dynamic equilibrium between several excited states to be demonstrated. 16,18 One of the fingerprints of the dynamic equilibrium is the reduction of the zero field splitting (ZFS) parameters of the triplet state, which is a well-known property of molecules with D 4h symmetry. 15,23,24 The averaging of the spectral parameters in these molecules occurs via vibronic interactions known as the Ham effect and serves as evidence of the dynamic Jahn-Teller effect.…”
Section: Introductionmentioning
confidence: 99%